Non-ionizing Imaging for the Emergency Department Assessment of Pediatric Minor Head Trauma - Cicogna, Alessia; Minca, Giulia; Posocco, Francesca; Corno, Federica; Basile, Cecilia; Da Dalt, Liviana; Bressan, Silvia (Frontiers in Pediatrics, 2022)
Minor blunt head trauma (MHT) represents a common reason for presentation to the pediatric emergency department (ED). Despite the low incidence of clinically important traumatic brain injuries (ciTBIs) following MHT, many children undergo computed tomography (CT), exposing them to the risk associated with ionizing radiation. The clinical predictions rules developed by the Pediatric Emergency Care Applied Research Network (PECARN) for MHT are validated accurate tools to support decision-making about neuroimaging for these children to safely reduce CT scans. However, a few non-ionizing imaging modalities have the potential to contribute to further decrease CT use. This narrative review provides an overview of the evidence on the available non-ionizing imaging modalities that could be used in the management of children with MHT, including point of care ultrasound (POCUS) of the skull, near-infrared spectroscopy (NIRS) technology and rapid magnetic resonance imaging (MRI). Skull ultrasound has proven an accurate bedside tool to identify the presence and characteristics of skull fractures. Portable handheld NIRS devices seem to be accurate screening tools to identify intracranial hematomas also in pediatric MHT, in selected scenarios. Both imaging modalities may have a role as adjuncts to the PECARN rule to help refine clinicians’ decision making for children at high or intermediate PECARN risk of ciTBI. Lastly, rapid MRI is emerging as a feasible and accurate alternative to CT scan both in the ED setting and when repeat imaging is needed. Advantages and downsides of each modality are discussed in detail in the review.